Samadhi Spa & Wellness Retreat: An Australian Case Study - Ramkissoon, Haywantee (Kendall Hunt Publishing Company, 2014)
Today, more than ever before, people desire to look and feel better, to slow the effects of aging, manage stress, and/or prevent age related illness. This growing social phenomenon is the so called wellness generation. Service Management in Health and Wellness Services examines the growing significance of the wellness concept as a feature of the health care industry. This new paradigm shift in the composition of health care and the subsequent changes in the needs and expectations of health care customers are transforming health care into a largely customer-driven service sector. Designed specifically for practitioners and students in the health and wellness industry, Service Management in Health and Wellness Services addresses various aspects from a services management perspective. In doing so, the publication reinforces that service management approaches can be used to effectively manage health and wellness services to provide customers with superior service and value. Those who conceptualize and manage the health care offering as essentially a ‘service’ offering will gain an advantage in the understanding of, and ability to deliver, service excellence. These concepts cover the full gamut of the health service and wellness industry – including operations, marketing, human resources, and more.